LINGUOCOGNITIVE ANALYSIS OF THE CONCEPTOSPHERE OF THE IDEAL HERO IN BEOWULF, ALPOMISH, ILYA MUROMETS BYLINA, AND BALLAD OF MULAN - Isroiljanova , Barno (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the conceptosphere of the ideal hero in different folk traditions using a linguocognitive approach. The study identifies semantic and cultural features of heroism. As a result, both universal and culture-specific aspects of the concept are revealed.